Physico-chemical changes during storage of litchi (Litchi chinensis) beverages - SINGH, PRABHAKAR; SINGH, I S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1986 and 1987 on storage of litchi (Litchi chinensis Soon.) beverages at Faizabad. There was a gradual decrease in organoleptic score and chemical changes during Their storage at room temperature. The ready-to-serve drink and nectar were acceptable up to 3 months. Squash could be maintained up to 4 months. Chemical change during storage led to the formation of off-flavour and discoloration of beverages